Corporate disputes in Ukraine: the application of the case-law of the european court of justice in Ukraine - Koruts, Uliana; Bazhenov, Mikhail (Актуальні проблеми правознавства, 2019)
The provisions of paper substantiate the necessity for the application of practice of the European Court of Justice in corporate disputes in Ukraine. The essence of the case law of the European Court of Justice is revealed. The necessity to fulfill obligations in the founding and activity of companies, corporate governance in accordance with the Association Agreement with the European Union is argued.